Challenges of Protecting Constitutional and Human Rights Against Anti-Terrorism Legislation (Comparative Study between The British and The Egyptian Regimes) - Abdelsalam, Noha Eissa Zakaria (Trinity College Dublin. School of Law. Discipline of Law, 2025)
The aim of this thesis is to compare, contrast and analyze the tension between freedom of expression and national security in the United Kingdom (the "UK") and Egypt. In particular, it examines the ways in which the UK and Egypt strike a balance between freedom of expression and national security in counter-terrorism law, specifically in relation to encouragement, incitement and glorification of terrorism. My central research question is: how can we respect freedom of expression, whilst ensuring that we also protect national security? In short, how can we protect rights whilst effectively countering terrorism? The thesis adopts a comparative methodology to examine two regimes which have different legal systems and are at different stages of democratic development. The UK is a common law system and an established democracy, while Egypt is a civil law country in transition from tyranny to democracy. I am seeking to identify the issues facing each regime based on the scale and nature of the risks threatening it. I aim to articulate the best approaches for balancing freedom of expression and national security based on constitutional law principles, i.e. the rule of law, the separation of powers and judicial review. I have delved into the study of constitutional law principles in pursuit of clear definitions of the boundaries limiting the distribution of powers between the branches of the state. I argue that one way of maintaining the rule of law while countering terrorism is to provide strong mechanisms of horizontal accountability within the state. `Horizontal accountability (...) refers to the capacity of state institutions to check abuses by other public agencies and branches of government'. In this thesis, I outline legitimate ways of balancing liberty and security, as appropriate to both a developed democracy like the UK and a country in transition to democracy like Egypt.
APPROVED